BACHELOR’S PROGRAM IN “INTEGRATED DESIGN” AND ITS IMPLEMENTATION IN INTERNATIONAL DESIGN SCHOOL AT COLOGNE UNIVERSITY OF APPLIED SCIENCES (Comparative Professional Pedagogy, 2021)
The paper is aimed at thorough studying and analysis of Bachelor’s program in “Integrated Design” in International School of Design (KISD) at Cologne University of Applied Sciences to outline positive features and aspects of the experience that can be borrowed for implementing similar programs in universities of developing countries. It has been defined that KISD Bachelor’s program in “Integrated Design” relies on study that goes beyond the traditional framework of design and combines different designer approaches, practice and techniques. It presupposes students’ work in at least ten out of twelve KISD branches of knowledge: Image and Motion, Identity and Design, Design for Manufacturing, Design Concepts, Design and Economy, Design Theory and Research, Gender and Design, Interface Design and Interaction Design, Ecology and Design, Production Technology, Service Design, Typography and Layout. Students’ professional orientation in KISD is organized in four stages: Discoveries; Connections; International; Focus. Additional requirement is a program-related aptitude test due to which students can demonstrate their aptitude to the program. Bachelor’s program in “Integrated Design” specialty offers 2 courses of study to students at the end of the first year of studying: “Integrated Studies in Design” and “European Studies in Design”. Study at the program of “Integrated Design” is project-oriented and organized in modules. Successful completion of the study program is verified by module exams throughout the whole study program and Final Exam (Bachelor’s thesis and Final Presentation). Exams can be of several types: oral, written, other (home assignments, a Study Journal (portfolio) etc.) and combined. The Defense takes place after the Presentation and is aimed at evaluating students’ abilities to present the work orally, independently explain and be aware of the practical application of the results of the Bachelor’s thesis; its subject-related and methodical aspects; interdisciplinary contexts; and interdisciplinary prospects. The procedure of calculating the final accumulative grade for the Bachelor’s exam has been described in detail.
Keywords: design; bachelor’s program; “Integrated Design”; modules; International Design School; Cologne; module project; module exam; Bachelor’s exam